Problems Faced by the School Teachers of Uttar Pradesh in the Transaction of Online Classes during COVID-19 Lockdown - Dvivedi, Sweta (SCHOOL SCIENCE, 2020)
The dreaded Coronavirus created a panic situation globally, and most of the countries across the world declared total lockdown. In India also, shutdown of activities was declared across the country, which included educational institutions too. The teaching-learning process was disrupted due to educational institutions’ closure, and online learning therefore was resorted to. The sudden shift of classes from physical to virtual mode impacted almost all education stakeholders, especially teachers, students, and parents. During online classes, the role, teaching style, timing, and norms also have been changed. A traditional classroom where no phones were allowed has now shifted to smartphones. The parents criticizing the demand of smartphones by children previously have purchased or given their own phones/tablets/laptops to their children to attend the classes. This haphazard shifting of classes from offline to online mode created chaos initially as guidelines were not clear. Some other issues were faced by the teachers at the commencement of the classes. The present paper explores the problems that Uttar Pradesh’s school teachers faced during online classes. A descriptive survey method was used in the study, and responses of 156 school teachers were collected.